The Urgency of the Diplomatic Role of the Indonesian Navy in Supporting Security Stability in the Indo-Pacific Region - Mayang Agneztia Parasasti; I Wayan Warka; Agus Adriyanto (CV. Rayyan Dwi Bharata, 2023)
Over the past few years, the intensity of use of the term